Fluid dynamics study on the effect of the maximum valve lift to the flow velocity at the intake valve of gasoline engine / Muhamad Razi Samsudin - Muhamad Razi , Samsudin (2019)
Intake valve lift height value plays a very important role in ensuring the power and performance of the ICE. Low lift valve will restrict the airflow into the engine cylinder. Less amount of air-fuel mixture will cause low energy combustion of ICE. Using high profile cam can increase airflow into the combustion chamber. However, increasing the valve lift beyond the maximum valve lift value will not give any additional flow of fluid into the combustion chamber. Higher lift often requires longer camshaft duration and increase valve train work, which can affect the performance and durability of the engine. Determining the optimum valve lift value is important to maintain the effectiveness and performance of the gasoline engine. Fluid flow studies around an intake valve in ICE are difficult to experiment with due to the position and size of small components moving at high speeds in the engine. Therefore, the use of CFD is the best method for this project. The analysis was conducted to determine the highest valve lift value that gives the highest air velocity into the combustion chamber at different intake valve diameter. Two (2) different engine`s cylinder head with 23 mm diameter intake valve size and 27 mm diameter intake valve size are used in the simulation. Each valve size profile is tested with nine (9) different valve lift height profile from one (1) millimeter (mm) valve lift to nine (9) millimeter (mm) valve lift. For 23 mm intake valve size, at the openings of 1 mm to 5 mm intake valve height, non-uniform airflow is detected around the opening of the valve. The more uniform flow fluid is detected at the valve openings starting at 6 mm to 9 mm. Fluid pressure in combustion chamber increase significantly between 1mm to 5mm valve opening. But no significant change of the combustion chamber pressure is seen when the valve lift is between 6mm and 9mm valve opening. For 27 mm intake valve size, at the openings of 1 mm to 3 mm intake valve height, non-uniform airflow is detected around the opening of the valve. The more uniform flow fluid is detected at the valve openings starting at 4mm to 9mm valve opening. Fluid pressure in combustion chamber increase significantly between 1mm to 3mm valve opening. But no significant change of the combustion chamber pressure is seen when the valve lift is between 4mm and 9mm. From the computational fluid dynamic simulations, result and analysis carried out, it was found that, for a 23 mm diameter valve size, the optimum valve lift required was 6 mm. Increasing the valve lift exceeds the 6mm value does not significantly increase the fluid volume entering into the engine cylinder during the intake cycle. For a 27 mm diameter valve size, the optimum valve lift required was 4 mm. Increasing the valve lift exceeds the 4mm value does not significantly increase the amount of fluid entering into the engine cylinder.